Analisis dan Penanganan Kerusakan Bantalan Gelinding pada Transmisi Cycloidal Disc Mesin Co-Extruder - Entus Abi Darda; Indra Tedjakumala (President University, 2016)
Abstract. This research is discribe about the analysis and damage handling of rolling bearings in the Cycloidal Disc transmission of Co-Extruder machine. Analysis of damage process is include all factors that cause damage to the bearings and identified by using a causal diagram. The identification results showed that the most dominant factor for damage to the bearings and eccentric bearings supporting the transmission of Cycloidal Disc of Co-Extruder machine is the lifespan of the bearings that are short. In the calculation of dynamic loading, the bearing support has a weight 21312.5 N and eccentric bearings have a load of 42.625 N with the age of 4.9 months and 15.9 months. Therefore, the investigation was done by load calculation that was to replace the pads with age calculation 20.000 work hours. From the calculation results obtained the supporting bearings and eccentric loading has age of 31.9 months and 62.4 months.Keywords. Analysis, Damage, Rolling bearing, Cycloidal Disc, Co-Extruder.